Bedside Transcatheter Patent Ductus Arteriosus Device Occlusion in an Extremely Low Birth Weight Neonate: A Novel Approach in a High-Risk Population. (27th October 2021) - Pouldar, Tiffany M.; Wong, Robert; Almeida-Jones, Myriam; Zahn, Evan; Lubin, Lorraine
Abstract : Extremely low birth weight (ELBW) infants weighing less than 1 kilogram are at a high-risk for delayed patent ductus arteriosus (PDA) closure. Percutaneous PDA closure offers a less invasive approach when compared with surgical PDA closure, which may provide faster recovery times and less transfusion requirements. However, this procedure involves transporting tenuous, unstable patients from the neonatal intensive care unit (NICU) to the catheterization laboratory which introduces many potential risks for the neonate. Performing percutaneous PDA closure at the bedside offers a successful alternative to performing the procedure in the catheterization laboratory and avoiding risk associated with transporting ELBW neonates.